Implementation of Public Speaking in the Mumarasah Extracurricular Program to Enhance Students' Independence and Self-Confidence - Saini, Mukhamat; Fauzi, Muhammad Umar; Chosi’ah, Chosi’ah (IERA, Islamic Education and Research Academy, 2024)
This study aims to: (1) explore the Mumarasah activities that distinguish Madrasah Tsanawiyah Yayasan Taman Pengetahuan (MTs YTP) Kertosono, (2) understand the process of public speaking activities or Mumarasah at MTs YTP Kertosono, (3) identify the strategies employed by MTs YTP Kertosono in training students' public speaking skills and how these strategies are applied to shape students' character, and (4) investigate the supporting and inhibiting factors of public speaking at MTs YTP Kertosono, Nganjuk. This research employs a qualitative descriptive approach to examine the implementation of Mumarasah activities in character development. Triangulation analysis is utilized by cross-checking the validity of the data with external sources to ensure the reliability of the findings. The results show that Mumarasah activities at MTs YTP Kertosono are aligned with character formation principles, including: (1) the principle of gradualism, (2) the principle of continuity, (3) the principle of momentum, (4) the principle of intrinsic motivation, and (5) the principle of guidance. The strategies and methods used by MTs YTP Kertosono to cultivate students' character through Mumarasah activities include: (1) role modeling, (2) instilling discipline, (3) habituation, (4) creating a conducive atmosphere, and (5) integration and internalization. These findings suggest that Mumarasah activities significantly contribute to shaping students' character by providing a structured environment that promotes active participation and the development of essential skills such as public speaking and self-discipline.